2015
DOI: 10.1152/japplphysiol.00313.2014
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory macrophages improve skeletal muscle recovery from ischemia-reperfusion

Abstract: The presence of macrophages (MPs) is essential for skeletal muscle to properly regenerate following injury. The aim of this study was the evaluation of MP profiles and their importance in skeletal muscle recovering from tourniquet-induced ischemia-reperfusion (I/R). Using flow cytometry, we identified two distinct CD11b(+) MP populations that differ in expression of the surface markers Ly-6C and F4/80. These populations are prominent at 3 and 5 days of reperfusion and molecularly correspond to inflammatory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 51 publications
4
36
1
1
Order By: Relevance
“…Increased collagen deposition in PEG-Fib and PEG-Fib/SDF-1α treated muscles may be indicative of M2 macrophage activity in the inflammatory setting. 70 These cells appear in the muscles as early as 3 days post-reperfusion 71 and produce arginase-1 and TGF-β factors both of which contribute to extra-cellular matrix deposition. 72 Overall, there appears to be no functional benefit from SDF-1α treatment up to 14 days post-TK-I/R injury compared to matrix delivery alone, despite apparent enhancement in neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Increased collagen deposition in PEG-Fib and PEG-Fib/SDF-1α treated muscles may be indicative of M2 macrophage activity in the inflammatory setting. 70 These cells appear in the muscles as early as 3 days post-reperfusion 71 and produce arginase-1 and TGF-β factors both of which contribute to extra-cellular matrix deposition. 72 Overall, there appears to be no functional benefit from SDF-1α treatment up to 14 days post-TK-I/R injury compared to matrix delivery alone, despite apparent enhancement in neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, there are 2 distinct subtypes of macrophages that can be distinguished by their surface marker expression. The F4/80 and CD11b markers are expressed by all macrophages, whereas Ly‐6C is highly expressed by the inflammatory macrophage subtype . In contrast, the anti‐inflammatory macrophage subtype expressed low levels of Ly‐6C and high levels of F4/80 .…”
Section: Methodsmentioning
confidence: 98%
“…activity (124,171) and contribute to the no-reflow phenomenon (62,63), increasing I/R-induced tissue damage. Macrophages reach the ischemic site 48 -72 h after reperfusion (68,170). Their exact role remains unclear, since they may be implicated in both I/R-induced tissue damage and recovery; Hammers et al (68) identified two prominent macrophage populations (inflammatory and anti-inflammatory) at 3 and 5 days of reperfusion.…”
Section: Phenomena Associated With Skeletal Muscle Injuries Followingmentioning
confidence: 99%
“…Macrophages reach the ischemic site 48 -72 h after reperfusion (68,170). Their exact role remains unclear, since they may be implicated in both I/R-induced tissue damage and recovery; Hammers et al (68) identified two prominent macrophage populations (inflammatory and anti-inflammatory) at 3 and 5 days of reperfusion. Noncellular factors, especially natural IgM, also mediate reperfusion injury by recognizing nonmuscle myosin heavy chain type II expressed during ischemia and activating the complement system (6,201).…”
Section: Phenomena Associated With Skeletal Muscle Injuries Followingmentioning
confidence: 99%